’˜HONEY OINTMENT’: A NATURAL REMEDY OF SKIN WOUND INFECTIONS - Tasleem, Samiyah; Naqvi, Syed Baqir Shyum; Khan, Saadat Ali; Hashimi, Khursheed (Journal of Ayub Medical College Abbottabad, 2011)
Background: Honey is a gift of nature, principally identified and valued to possess antimicrobial and anti-inflammatory activity and has been used as a natural remedy of wounds since ancient times. The objectives of this study were to evaluate the antimicrobial activity of honey against micro-organisms, to formulate a honey ointment and to evaluate the efficacy of such ointment by conducting clinical trials on skin wound infection. Methods: This experimental study was conducted at Department of Pharmaceutics, Faculty of Pharmacy, University of Karachi and Out-patient Department of Dermatology, Fauji Foundation Hospital, Rawalpindi from November 2009 to October 2010. The antimicrobial activity of Pakistani floral sources (Trachysperm copticum, Acacia nilotica species indica, Zizyphus) honey samples was investigated by disc diffusion method against freshly isolated wound infecting bacteria (Staphylococci aureus, Staphylococci epidermidis, Streptococcus faecalis, Pseudomonas aeruginosa, Klebsiella pneumonia, Escherichia coli, Proteus vulgaris and Candida albicans), and Staphylococci aureus ATCC 6538, Pseudomonas aeruginosa ATCC 9022, Escherichia coli ATCC 25922, Candida albican ATCC 15146. An ointment containing 20% active antimicrobial honey was formulated. The efficacy of such ointment was evaluated by passing thought clinical trials. A total number of 27 patients (23 skin wound infection, and 4 diabetic foot ulcer) were involved in the study. Thin layer of newly formulated honey ointment on gauze were applied two to three times per day till complete healing. Results: In microbiological assay the honey samples were found to exhibit a very promising antimicrobial activity against all the micro-organisms tested. In clinical trial very significant results (99.15%) healing was observed in skin wound infections cases with mean healing time of 5.86 (2-20) days, and 95% diabetic foot ulcers healed with the mean healing time of 20 (8-40) days. Conclusion: Newly formulated ointment containing 20% active antimicrobial honey is very effective and alternative low-cost product for the treatment of wound infections. Keyword: antimicrobial activity, honey ointment, wound infection, diabetic foot ulcer